The Role of Sustainable Human Resource Management Practices in Developing Sustainable Innovation - Nugaela, Melaka (My University, 2025)
Social and environmental challenges have created complex competitive environments while simultaneously encouraging companies to accept environmental and social responsibility towards people and planet. Companies are increasingly focusing on sustainable innovation to address global expectations and challenges. Sustainable Human Resource Management (SHRM) plays a key role in developing innovative culture within organizations. This research explores on the influence of sustainable human resource practices on the generation of sustainable innovation. A qualitative case study approach was chosen, employing semi-structured interviews and documentation analysis. This study focuses on three core aspects of Sustainable Human Resource Management (SHRM), ecological, social and strategic. The ecological aspect of SHRM incorporates recruitments that are environmentally oriented, green trainings, performance evaluations which are sustainability focused and reward systems that are ecologically motivated which will eventually promote employee engagement in the sustainable initiatives. Social aspect of the SHRM emphasizes on the topics such as safety in workplaces, mental wellbeing, diversity, equity and inclusion and contribution to corporate social responsibility. Supportive environment within the organization will be created by fostering to these evaluations which will enhance the employee commitment towards creativity and team collaboration. The strategic aspect of SHRM highlights the importance of adaptation and innovation in the long-term planning by developing the leadership, an efficient HR, aligning HR policies, and proving job security. These practices contribute to sustainable innovations by cultivating a sustainability-conscious workforce. The findings of this research reveal how ecological, social and strategic aspects of SHRM influence sustainable innovation across three stages, namely operational optimization, organizational transformation and system building. SHRM plays a significant role in influencing organizations to pursue a sustainable competitive advantage by integrating people management into innovation strategies.
Keywords: Sustainable Human Resource Management, Sustainable Innovation, Operational Optimization, Organizational Transformation, System Building